2020
DOI: 10.1002/pds.5135
|View full text |Cite
|
Sign up to set email alerts
|

CPRD Aurum database: Assessment of data quality and completeness of three important comorbidities

Abstract: Purpose: The Clinical Practice Research Datalink (CPRD) now provides a new medical record database, CPRD Aurum. This is the second of several studies being undertaken to assess the quality of CPRD Aurum data for research. Methods: We included patients aged 20+, with at least one lab test result of any type from a random sample of 50 000 patients in CPRD Aurum. We assessed whether diagnosis codes for type 2 diabetes, hyperlipidemia, and iron deficiency or unspecified anemia were accompanied by supporting codes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 9 publications
1
39
0
Order By: Relevance
“…The findings of this study are consistent with two prior assessments conducted in this same data sample: 10 , 11 diagnoses recorded in CPRD Aurum are of relatively high correctness for use in medical research; however, completeness may not be sufficient for all research questions. When using CPRD Aurum data, researchers should consider study design choices or the addition of linked data.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The findings of this study are consistent with two prior assessments conducted in this same data sample: 10 , 11 diagnoses recorded in CPRD Aurum are of relatively high correctness for use in medical research; however, completeness may not be sufficient for all research questions. When using CPRD Aurum data, researchers should consider study design choices or the addition of linked data.…”
Section: Discussionsupporting
confidence: 86%
“…This 50,000-patient sample was also used for additional validation studies on CPRD Aurum data that describe other data elements and outcomes. 10 , 11 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CPRD is well suited for the study of diabetes, as long‐term management of people with type 2 diabetes is primarily handled by general practitioners in the UK 18 . In addition, a recent study revealed 99% correctness and 94%–98% completeness for diagnoses related to type 2 diabetes in CPRD Aurum, 19 and other laboratory measures have also been validated in the CPRD 20 …”
Section: Methodsmentioning
confidence: 99%